Novel Plan for Stripping Gas Recovery in Gas Dehydration Unit: Techno-Economical Evaluation for Khark Petrochemical Company as A Case Study - Abdehvand, Arman M.; Haghi, Mahdi; Ansari, Aminreza; Hoseinirad, Ebrahim (Journal of Petroleum Research and Studies, 2025)
The presence of water vapor in natural gas presents several challenges, including corrosion, pipeline blockages, and reduced pipeline capacity. Gas dehydration is therefore a critical process for reducing water content and mitigating these issues. In this study, the dehydration unit of Khark Petrochemical Company (KPC), which utilizes triethylene glycol (TEG) as the desiccant agent, was simulated using Aspen HYSYS v11.0. The innovation of this paper lies in proposing an optimized method for recovering vent gas used in the glycol solution regeneration process, which has been thoroughly evaluated from both technical and economic perspectives. Simulation results were validated in comparison to plant Process Flow Diagram (PFD) data. A sensitivity analysis was then performed to identify and investigate the impact of various parameters on the dehydration unit's performance and the produced dry gas. Increasing the solvent circulation rate, stripping gas flow rate, and reboiler temperature improves the water removal rate, as indicated by the results. Several options for recovering around 0.7 MMSCFD of stripping gas from the regeneration tower by raising the regenerator's operating pressure were evaluated, with estimated capital and operating expenditures for each. The optimal option, which routes the recovered stripping gas to a low-pressure feed gas compressor, has an estimated capital cost of $80,000 based on Aspen ICARUS software and additional costs were calculated as a percentage of the equipment price. This option, by preventing gas waste and converting it into methanol with an operational cost of approximately $67000, generate annual revenue of $1.7 million. The amount of emission reduction achieved through gas recovery is equivalent to 48 tons of CO₂ per day.